GCA consultant scheduling software - Kozicki, Drew A. (My University, 2010)
Since the opening of the GCA computer labs at the University of Wisconsin La Crosse, the scheduling of the lab consultants has been done manually. At the start of the scheduling process, each consultant in turn, based on seniority, is assigned a time slot where he or she can come into the head consultant's office to sign up for hours in the labs. The head consultant then enters the schedule in an Excel spreadsheet and posts the schedule online. Throughout the semester, if a lab consultant needs to take a shift off, they must enter a request in a designated forum and another lab consultant must state that he or she will pick up the shift. Using the forum to accomplish this task requires that other consultants check for available shifts on a regular basis. This process often leaves labs without consultants since consultants often do not check the forum. On the administrative side, this process is time consuming to manage. If a shift is left uncovered, the manager must search the forums to see who was supposed to cover the shift. No rules are in place limiting the number of times the consultant covering a shift can change, which causes the tracking of a shift to be a "connect the dots" puzzle. This makes tracking and disciplining the consultant responsible for the shift a time consuming process. This paper describes a software application designed to provide administrative support for the scheduling of GCA consultants. The application was developed at the University of Wisconsin La Crosse in coordination with the GCA department. The application provides the consultants with the ability to: view lab schedules, sign up for shifts, request shifts off, and sign up for notifications of open shifts. The application provides the head consultant with the ability to: create and edit lab schedules, assign shifts to consultants, monitor consultant activity, and view shift reports.
Keywords: Computers and college students; Application software -- Development; Scheduling -- Software